PENGARUH BABY MASSAGE TERHADAP KUALITAS TIDUR BAYI USIA 3 – 6 BULAN DI DESA SIDOASRI - Holti Felika Agustin; Raden Maria Veronika Widiatrilupi (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2025)
The quality of baby's sleep affects the growth and development of the baby. Babies with good sleep quality have optimal growth and development. According to research, there are around 44% of babies who experience sleep disorders. One of the non-pharmacological therapies to overcome baby's sleep problems is baby massage. This study aims to determine the effect of baby massage on the quality of sleep of babies aged 3-6 months in Sidoasri Village. This study is included in quantitative research using the Pre Experimental research model with a one group pretest posttest research design. The sample in this study was 16 respondents. The data collection technique used the Brief Infant Sleep Questionnaire (BISQ) checklist sheet. The data analysis used was the Wilcoxon Signed Rank test. The results of the Wilcoxon test obtained a p value (0.002) < alpha (0.05), meaning that there is an effect of baby massage on improving the quality of sleep of babies aged 3-6 months in Sidoasri Village. Baby massage is needed by babies to provide a sense of comfort and relaxation to the baby's body so that the baby can sleep better and have good sleep quality.